Impact of Hydrogen-Enriched Natural Gas on the Accuracy of Odorant Measurements - Giorgio Ficco; Viviana Cigolotti; Gino Cortellessa; Giulia Monteleone; Marco Dell’Isola (Sensors, 2025)
Blending hydrogen with natural gas is emerging as a pivotal strategy in the transition to low-carbon energy systems. However, the exploitation of the natural gas infrastructure to distribute natural gas and hydrogen blends (and 100% hydrogen in the long-term) introduces several technical, economic, and safety issues. These latter are paramount, especially in urban distribution networks that supply residential buildings and dwellings, since the quality and safety of the living environment can also be significantly affected. In this scenario, the reliability of odorant concentration measurements according to the best practices currently in use for natural gas becomes crucial. This study is aimed at assessing the accuracy of odorant measurements at different concentration levels (i.e., low, medium, and high) in 100% methane, methane–hydrogen blend and 100% hydrogen. The obtained results show the tendency to overestimate the odorant concentration up to 2.3% in methane–hydrogen blends at medium and high concentrations of THT as well as the underestimation of −3.4% in 100% hydrogen at low concentration of TBM. These results are consistent with those of natural gas from the city distribution network with hydrogen content of 5% and 20%.